Long-term ecological analysis of Anguillicola crassus occurrence and impact on the European eel population in a Mediterranean lagoon (North Italy) - Giari L.; Castaldelli G.; Gavioli A.; Lanzoni M.; Fano E. A. (Estuarine, Coastal and Shelf Science, 2021)
Anguillicola crassus, a haematophagous nematode infecting the eel swim bladder, was introduced into Europe from Asia in the early 1980s with imported Anguilla japonica. It spread rapidly after establishment in the native European eel Anguilla anguilla. A long-term dataset shows the dynamics of A. crassus in eels of the Comacchio Lagoon from 1997 to 2019, and reveals the factors that influence its prevalence. A sample of 339 eels showed 19 parasitized by adult A. crassus, with one to five parasites per infected host and a mean abundance of 0.09 ± 0.45. Prevalence ranged from 2.14% (minimum value reached in 2005/06) to 11.9% (maximum reached in 1997). No significant temporal trend in the occurrence of A. crassus was detected over the period of the investigation, which was characterized by low levels of infection compared to that in eel populations from other coastal lagoons or estuaries. No influence of A. crassus on condition factor, hepatosomatic and gonadosomatic index and swim bladder integrity (evaluated through the Swim bladder Degenerative Index) was found, suggesting a minimal impact of the parasite on the eel population health. Anguillicola crassus, although established in Comacchio Lagoon, has not become invasive. The possible reasons for this, among which high salinity, will be discussed. Management of the lagoon for the past 30 years has also contributed to parasite containment through avoidance of restocking the eel population from external sources.